Community-Based Mobile Self-Assessment for Tuberculosis Screening Among Parents and Children: A Cross-Sectional Study - Warastuti, Widya; Sulistyowati, Reny; Ariestini, Tri Ratna (Chakra Brahmanda Lentera Institute, 2026)
Background: Conventional tuberculosis screening is often limited by reporting delays and low accessibility. This study evaluates a digital solution to address this gap by integrating behavioral assessment and screening of two populations into a single community-based platform. The study aimed to evaluate the NOR TBC mobile app in identifying suspected tuberculosis cases and analyze the relationship between cognitive factors and preventive behaviors. Methods: This cross-sectional observational study followed STROBE guidelines. Using convenience sampling, 70 parents, were recruited. Data were collected via the app’s integrated modules for Knowledge, Attitude, and Practice and self-screening. App quality was validated using ISO 25010 and expert review. Data were analyzed using descriptive statistics and Chi-Square tests (p < 0.05). Results: The NOR TBC mobile identified 5.7% adult and 14.3% child presumptive TB cases. Technical evaluation rated the app as